Inhibitory activity of fermentates towards Zygosaccharomyces bailii and their potential to replace potassium sorbate in dressings. (June 2017) - Samapundo, S.; de Baenst, I.; Eeckhout, M.; Devlieghere, F.
Abstract: The major objective of this study was to assess the application of commercially available 'clean label' fermentates as preservatives in dressings. This study was performed in two parts. In the first, the inhibitory activities of the reference preservative (potassium sorbate) and selected fermentates – MicroGARD ® 200, Nabitor, Nabitor WS, Biogard ND, Defence AM-P and Polyfence™ 35TD - towards Zygosaccharomyces bailii were assessed as a function of pH (3.5–5.0) on Sabouraud agar. In the second part, challenge, shelf-life and sensorial tests were used to determine the potential of selected fermentates to replace potassium sorbate in dressings. All preservatives had significant ( p < 0.05) pH dependent inhibitory activities towards Z. bailii . Significant ( p < 0.05) synergistic interactions were determined to occur between pH and the concentration of all preservatives. The challenge, shelf-life and sensorial tests showed that Polyfence 35TD ≥ 1% could be used to replace potassium sorbate in dressings without compromising the microbial stability and sensorial quality of the product. The results of these tests also show that careful considerations have to be made when fermentates are used to replace potassium sorbate (or other chemical preservative) in dressings as the shelf-stability and sensorial properties can be altered. Highlights: Inhibitory activity of commercial fermentates towards Z. bailii was evaluated. All fermentates had significant inhibitory activities towards Z. bailii . Synergistic interactions occurred between pH and concentration of the fermentates. Polyfence™ 35TD and MicroGARD ® 200 were the most inhibitory fermentates. Polyfence 35TD at ≥1% can be used to replace potassium sorbate in dressings.